Ebtanas SMUdan UMPTN Sebagai Bottleneck: Perlunya Pembaruan Kebijakan Penidikan yang Rasional - Yana Karyana (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2001)
As an instrument to gauge the competence and competition in learning process, Ebtanas (Standard National Grades) and UMPTN (Admission Test for State Universities) in Indonesian education system have changed into a myth of schooling. Not only that the Ebtanas and UMPTN have become the aims of schooling, but also become "traffic lights" that direct schools' management. In the schools, teachers always encourage students to be successful in Ebtanas and UMPTN tests. They make Ebtanas and UMPTN as the only reference and guideline. Other subjects such as religion, morals, culture and literary apreciation, and personality development -- the important fundamentals for affective education -- are ignored. At the same time, parents and the society generally perceive school cis a place for their children to drill their children to be. able to compete in achieving a good Ebtanas Standard Grade (NEM) and a success in UMPTN. The Ministry of Education makes the NEM and UMPTN as the only indicators of the success of schooling. The educational policy flaws are aggravated by other policy failures with 1994 Curriculum, which over-emphasising on formal schools of SLTP and SMU. Other vocational schools (SMK) that are in better position to provide employment and support economic development are generally marginalised. With the Curriculum 1994, all of the SLTP, SMU, and SMK students' achievement is measured by the NEM, and later by the UMPTN for entering the state universities. Consequently, the number of students who want to be enrolled in universities is not followed by the capacity. There is no doubt that Ebtanas and UMPTN constitute the bottleneck. There is a "university intoxicated zone" that must be corrected by: ( 1) Reconstructing Ebtanas and UMPTN simultaneously to create a rational flow to the university, and (2) To change the fundamental policy for higher education. It is urgently required that the government give a fair playing field to the formal as well as vocational schools.